The innovative sale : [unleash your creativity for better customer solutions and extraordinary results] - Donnolo, Mark (AMACOM, American Management Association, 2014)
In this groundbreaking book on sales creativity, readers will learn how to integrate the right-brain aptitude for innovation with the left-brain affinity for logic and process. The result is a fresh, dynamic approach that addresses customers' needs while expanding the salesperson's entire way of thinking. Packed with real-life examples and powerful principles.